THE IMPACT ON FARM PROFITS OF A COMPANY’S PARTNERSHIP WITH A POTATO FARM - Hirwan Hamidi (Journal of Indonesian Economy and Business (JIEB), 2014)
This research aims to explain the impact of the partnership on potato farms’ profits in Sembalun District, West Nusa Tenggara Province. To achieve this goal, we looked at 142 farmers, comprising of 111 partnered farmers and 31 non-partnered farmers. The conclusions from our profit function analysis were: (i) the partnership had a positive impact on potato farmers’ profits in Sembalun District, West Nusa Tenggara Province; (ii) productivity, input costs, and labor costs had a significant influence on profits as an impact of the partneship. In this context, it is recomended that the local government encourage and facilitate potato farmers who have not yet established a partnership to enter such an arrangement with the company, so that their productivity and incomes increase. In addition, the local government is expected to build storage facilities for potato seeds. Future research should search for potato seeds that can replace the imported ones.